A label-free fluorescence assay for potassium ions using riboflavin as a G-quadruplex ligand1. Issue 10 (21st May 2015) - Xu, Lijun; Sun, Na; Zhou, Lu; Chen, Xing; Wang, Jine; Wang, Qinglin; Wang, Kewei; Zhang, Jianye; Pei, Renjun
<x xml:space="preserve">Abstract</x> A label-free fluorescence K+ assay was developed using riboflavin, a new G-quadruplex ligand, and a G-quadruplex sequence (PW17).